(untitled) (Mūzikas akadēmijas raksti, 2024)
Many aspects of music have been, for a long time, reflected in comprehensive theoretical teachings (e.g. harmony, musical form, instrumentation). However, at this time, there still is no similar kind of teaching or doctrine for counterpoint. There has only been study of the so-called ‘invertible counterpoint’ (mainly as an element of two-part texture). However, it is evident that there has not been enough study and classification of polyphony itself and the simpler form of counterpoint. In his Gradus ad Parnassum, Johannes Joseph Fux has described species counterpoint from the point of view of harmony (its consonances and dissonances: Fux 1725). Later, Ernst Kurth emphasized the melodic nature of voices in his Grundlagen des linearen Kontrapunkts. Nowadays, there are many vital questions regarding a wide range of contrapuntal aspects.